Factores maternos: edad, grado de instrucción, ocupación y actividades sobre estimulación temprana y desarrollo psicomotor en niños menores de un año. Csmi Santa Lucia de Moche, 2009 - Cárdena Amador, Jaritza Gisella (2009)
This research study, descriptive, correlational and cross-sectional was conducted during the months of March to June 2009, in the town of Moche, in order to determine the relationship between maternal factors: age, level of education, occupation and activities on early learning and psychomotor development in children under one year. The sample consisted of 66 mothers and their infants under one year. For data collection we use two instruments: Survey to Determine Maternal Early Stimulation Activities (EDAMET) developed by the authors of this study, and the Scale for Assessment of Psychomotor Development (EEDP), developed by Rodriguez and Col. (1974 ). The results are presented in league tables of single and double frequency input numeric / percentage, as well as statistical graphics. The analysis of the relationship between variables was conducted by independent testing criteria Chi Squares. From the discussion of the results we got these conclusions: 1. All study mothers, 62.1 percent are adults, 47 percent have high school education, 77.3 percent work at home and 87.9 percent made appropriate early learning activities for the kids. 2. The psychomotor development is normal in infants by 84.8 percent, 13.6 are at risk and 1.5 percent retardation. 3. There is no significant relationship between maternal factors: age and occupation with psychomotor development. 4. There is highly significant relationship between maternal factors: level of education and early learning activities with the infant psychomotor development.